The datafication of media: Big data and the media industries. (1st March 2017) - Arsenault, Amelia H.
The datafication of media and the application of big data services to that data are facilitating new forms of networked associations between media companies. Moreover, big data represents an emerging global format, theoretically analogous to the global proliferation of television formats; media organizations around the world are using big data in an effort to compete in a globalized media marketplace and to better tailor content to local audiences. The article argues that these two interrelated trends have intensified the merging of Internet networks and communication networks, creating new centres of power – not based on control of content but on control of data. The first section provides theoretical and historical context surrounding the proliferation of big data within media industries. The second section examines how 'hyperscale' big data networks are solidifying the relationships between large Internet companies and media companies. The article concludes with an exploration of how big data have emerged as a global format in the media industries.